Pengaruh Label Halal terhadap Keputusan Pembelian Produk Kosmetik Wardah - Siti Nurmaya Adianti; Febrima Ayuningrum (STEBI Global Mulia Cikarang, 2023)
Cosmetics is one of the products offered to meet the secondary needs and desires of consumers, in order to appear more beautiful and attractive. Because the majority of the population in Indonesia adheres to the Islamic religion with a Muslim population reaching 86.9%, therefore certainty about product halalness is an important thing to pay attention to. The development of halal cosmetics in Indonesia has grown quite significantly. This is marked by the emergence of cosmetic companies with various brands. The cosmetic brand that is quite well-known in the community is Wardah. This study aims to determine how the influence of the halal label on the decision to purchase Wardah cosmetic products. In this study the authors used the label theory according to Philip Kotler and Garry Armstrong (2010) and the purchasing decision theory according to Tjiptono (2011). The method used in this study is a quantitative method by distributing questionnaires. Subjects in this study used a sample of 86 respondents. Sources of data used in this study are primary and secondary data. The data analysis method used in this study is the data normality test, data linearity test, simple regression test and t test using IBM SPSS 22. The results of this study indicate that the Halal Label (X) influences Purchase Decision (Y). The results in the test can be seen from the results of the simple linear regression test, it can be seen that the results of the significance of t are 0.000 <0.05 so that H0 is rejected and Ha is accepted. This shows that the Halal Label variable (X) has a significant effect on Purchase Decision (Y). And it can also be seen from the t count of 14.517 which means the t count is greater than the t table of 1.992.